Postharvest Treatment of Guava (Psidium guajava L.) Fruits with Boric Acid and NAA for Quality Regulation during Ambient Storage - Singh, Jatinder; Prasad, Narendra; Singh, Shailesh Kumar (International Journal of Bio-resource and Stress Management, 2017)
Guava fruit exhibits a climacteric pattern of respiration and ethylene production so is highly perishable in nature and suffers great extent of post-harvest loss. Storage of guava fruits by using chemicals like GA3, Salicylic acid, NAA, potassium permanganate and boric acid as postharvest treatment is commercially acceptable and economically feasible. The present investigation was carried out with objective to compare the efficacy of boric acid and NAA and their most effective concentration for shelf-life enhancement of guava fruits in winter season. The fruit of guava, cv. Allahabad Safeda were harvested, selected for uniformity of size, colour and diseased fruits were discarded. Prior to the application of post-harvest treatments, destalking of the fruits was done by retaining only 0.5 cm long pedicels in each fruit. The destalked guava fruits were sorted and pre cooled in running water for 12−15 minutes. Fruits were treated with Boric acid @ 100 ppm, 200 ppm and 300 ppm, NAA @ 200 ppm, 300 ppm and 400 ppm for 1−2 minutes. The physical parameters like fruit size, fruit weight, physiological weight loss, decay of fruits and specific gravity; chemical parameters like TSS, titratable acidity, ascorbic acid and sugar content; and palatability rating were observed and compared with untreated fruits. Both, boric acid and NAA, had significantly affected the shelf life of guava fruits stored under ambient condition. Boric Acid 200 ppm and 300 ppm were equally effective, similarly NAA 300 ppm and 400 ppm were equally effective for quality retention in guava fruits.